2009
DOI: 10.3727/154296610x12686999887328
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Sequestration by <I>Spirulina Platensis</I> in Photo-Bioreactors

Abstract: Spirulina platensis was cultivated at small scale in photobioreactors for CO 2 sequestration experiments carried out at different CO 2 concentrations within the range 0.5 to 10%, temperatures 10 to 40 o C and light intensities 60 to 200 μmol s -1 m -2. CO 2 sequestration effi ciency of achieved 99.9 %, specifi c growth rate, doubling time, rate of CO 2 sequestered into the algal cells and small changes of pH found for each batch experiment. Spirulina Platensis adapted to a novel nutrient solution was cultivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…14 - [39] Although different algal species are reported to withstand high concentrations of CO 2 , their enhanced growth and maximum biomass yield are largely observed only at CO 2 concentrations of 10-40%. Many studies indicate that the CO 2 concentration alone cannot be directly correlated to biomass productivity, but other factors such as the tolerance limit of algae to CO 2 and its utilization rate also play key roles in algal productivity [22,[40][41][42]. Furthermore, high photosynthetic efficiency of microalgae converts CO 2 to biomass rich in carbohydrates such as starch, cellulose, and various fermentable sugars via Calvin cycle [34,43], which is followed by metabolic pathways such as glycolysis and TCA cycle, resulting in lipid biosynthesis, stored as triacylglycerols and protein synthesis (Figure 1).…”
Section: -[33]mentioning
confidence: 99%
See 1 more Smart Citation
“…14 - [39] Although different algal species are reported to withstand high concentrations of CO 2 , their enhanced growth and maximum biomass yield are largely observed only at CO 2 concentrations of 10-40%. Many studies indicate that the CO 2 concentration alone cannot be directly correlated to biomass productivity, but other factors such as the tolerance limit of algae to CO 2 and its utilization rate also play key roles in algal productivity [22,[40][41][42]. Furthermore, high photosynthetic efficiency of microalgae converts CO 2 to biomass rich in carbohydrates such as starch, cellulose, and various fermentable sugars via Calvin cycle [34,43], which is followed by metabolic pathways such as glycolysis and TCA cycle, resulting in lipid biosynthesis, stored as triacylglycerols and protein synthesis (Figure 1).…”
Section: -[33]mentioning
confidence: 99%
“…erance limit of algae to CO2 and its utilization rate also play key roles in algal productivity [22,[40][41][42]. Furthermore, high photosynthetic efficiency of microalgae converts CO2 to biomass rich in carbohydrates such as starch, cellulose, and various fermentable sugars via Calvin cycle [34,43], which is followed by metabolic pathways such as glycolysis and TCA cycle, resulting in lipid biosynthesis, stored as triacylglycerols and protein synthesis (Figure 1).…”
Section: -[33]mentioning
confidence: 99%
“…Therefore, the rate of CO2 biofixation per initial inoculation mass of microalgae can be determined by Eq. 5 rCO2 = RCO2/Xo (5) where RCO2 [gCO2 L -1 d -1 ] is the biofixation rate and rCO2[gCO2 g -1…”
Section: Determination Of Growth Rate and Kinetic Parametersmentioning
confidence: 99%
“…By 2100, 26 billion tons of CO2 are estimated to be released into the atmosphere from anthropogenic sources 3 . Photosynthetic organisms such as microalgae species are potent producers of value-added bioactive compounds such as pigments, vitamins and long-chain polyunsaturated fatty acids, when grown under stress conditions can accumulate significant quantities of total lipids [4][5][6] . Recent studies indicated that improvements in culture conditions are needed to obtain adequate productivity of lipid, protein, carbohydrate content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation